PENGARUH KECERDASAN SOSIAL TERHADAP PRESTASI BELAJAR SISWA DI SMK NEGERI 2 KOTA JAMBI - Resi Adelina Manulang (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
This Research aim to to know influence of intellegence of social to achievement learn student and give input to teachers so that always motivate its students to develop potency or its ability to be created to feel self confidence and train on how to to look for spirit. This research have the character of descriptive qualitative by using method spreading of scale enquette of likert by determining variable, indicators of variable and also formulate item with each question of instrument deskriptor, research qualitative refer at research as a means of compiler of data to get conducted authenticity. Pursuant to data analysis which have been executed with technique analyse intellegence of achievement and social learn student. Result of this research indicate that intellegence of social have an effect on to achievement learn student in SMK Country 2 Town Jambi. This can be shown by using formula of product moment obtained by 0.4065 is later;then tested by using formula of t, pursuant to its calculation is obtained result 2.849 meaning t calculate > t of is tables of or 2.849 > 2.020.Keyword : Social Intelligence, Learning achievement (Inter Personal Quotient)